Capitalizing on Learners’ Individuality: From Premise to Practice, Authors: Tammy Gregersen and Peter D. MacIntyre, Publisher: Multilingual Matters, 2014, ISBN: 978-1-78309-119-5, Pages: 260 - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2014)
Book review